A method for increasing the capacity of lithium battery positive electrode material and a large-capacity lithium-ion battery
By introducing materials with high reversible lithium storage theoretical capacity and low reversible lithium storage potential in the preparation process of lithium-ion battery positive electrode materials to form a composite positive electrode material with a core-shell structure, the problem of insufficient capacity and energy density of existing lithium-ion battery positive electrode materials is solved, and the capacity and energy density of lithium-ion batteries is improved.
Patent Information
- Application Number
- CN202110323807.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-03-26
AI Technical Summary
The capacity and energy density of the cathode materials of existing lithium-ion batteries are difficult to meet the growing demand, especially in materials with high reversible lithium storage theoretical capacity and low reversible lithium storage potential.
By introducing materials with high reversible lithium storage theoretical capacity and low reversible lithium storage potential, such as silicon, graphene, etc., in the preparation process of the positive electrode material, a composite positive electrode material with a core-shell structure is formed, so that it is tightly wrapped by traditional positive electrode materials to build an isopotential body.
The reversible lithium storage potential of silicon-based or carbon-based materials wrapped in traditional cathode materials is improved, so that it can reversibly store lithium at a higher potential, thereby achieving an increase in the capacity and energy density of lithium-ion batteries.
Smart Images

Figure CN115132976B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for increasing the capacity of a lithium battery positive electrode material and a large-capacity lithium ion battery. Background Art
[0002] Commercial lithium-ion battery cathode materials, such as cobalt-based or nickel-based layered metal oxides LiCoO2 (LCO), LiNi x Co y Mn z O2(NCM), LiNi x Co y Al z O2 (NCA), and olivine structure LiFePO4 (LFP) have increasing demands for capacity and energy density. Therefore, the development of new secondary batteries, especially new cathode materials, is a top priority. Carbon-based and silicon-based materials have high theoretical capacity, but because of their low reversible lithium storage redox potential, they are used as negative electrodes for lithium-ion batteries.
[0003] A Faraday cage is an equipotential body with zero internal potential difference. Therefore, by constructing a core-shell composite positive electrode material, it is expected to construct an equipotential body by encapsulating silicon-based or carbon-based materials with high theoretical reversible lithium storage capacity with commonly used traditional positive electrode materials, thereby increasing the reversible lithium storage potential of the silicon-based or carbon-based materials encapsulated inside the traditional positive electrode material, achieving reversible lithium storage at a relatively high potential, and then obtaining additional capacity, thereby improving the capacity and energy density of the composite positive electrode material. Summary of the invention
[0004] The purpose of the present invention is to provide a method for increasing the capacity of a lithium battery positive electrode material and a large-capacity lithium-ion battery constructed using the method, which can improve the capacity and energy density of the lithium-ion battery.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for increasing the capacity of positive electrode materials for lithium batteries comprises introducing materials with high theoretical reversible lithium storage capacity and low reversible lithium storage potential during the preparation of positive electrode materials to obtain a composite positive electrode material with a core-shell structure.
[0007] A method for improving the capacity of a lithium battery positive electrode material, wherein the specific composition of the core-shell composite positive electrode material is that a material with a high reversible lithium storage theoretical capacity and a low reversible lithium storage potential is tightly wrapped by the positive electrode material.
[0008] Optionally, the material with high reversible lithium storage theoretical capacity and low reversible lithium storage potential used to prepare the core-shell composite positive electrode material is one or more of silicon, graphene, graphene oxide, graphite, graphite oxide, germanium, tin, phosphorus, and antimony.
[0009] Optionally, the positive electrode material is one of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material, and nickel-cobalt-aluminum ternary material.
[0010] A large-capacity lithium-ion battery comprises a positive electrode and a negative electrode, wherein the positive electrode is a core-shell composite positive electrode material prepared by the method for improving the capacity of a lithium battery positive electrode material according to any one of claims 1 to 4.
[0011] Optionally, the negative electrode material is one of graphite, carbon-silicon composite material, metallic lithium, graphene, and graphene oxide.
[0012] It can be seen from the above technical scheme that the present invention utilizes the high capacity of silicon-based, carbon-based and other materials, introduces silicon-based, carbon-based and other materials into the preparation process of traditional lithium-ion battery positive electrode materials, and wraps the silicon-based, carbon-based and other materials with high reversible lithium storage theoretical capacity with commonly used traditional positive electrode materials. Since the composite material as a whole is an equipotential body, the reversible lithium storage potential of the silicon-based or carbon-based materials wrapped in the traditional lithium-ion battery positive electrode material will be improved, so that the silicon-based, carbon-based and other materials can reversibly store lithium at a higher potential, such as Figure 1 As shown, this provides additional capacity to the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Schematic diagram of the mechanism of additional reversible lithium storage of the core-shell composite positive electrode material prepared in Example 1.
[0014] Figure 2 This is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 5 and the lithium-ion battery assembled in Comparative Example 1;
[0015] Figure 3 This is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 6 and the lithium-ion battery assembled in Comparative Example 2;
[0016] Figure 4 This is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 7 and the lithium-ion battery assembled in Comparative Example 3;
[0017] Figure 5 This is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 8 and the lithium-ion battery assembled in Comparative Example 4;
[0018] Figure 6 cyclic voltammetry comparison diagram of the lithium ion battery assembled in Example 5 and the lithium ion battery assembled in Comparative Example 1;
[0019] Figure 7It is a differential comparison diagram of constant current charge and discharge curves of the lithium ion battery assembled in Example 5 and the lithium ion battery assembled in Comparative Example 1;
[0020] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. DETAILED DESCRIPTION
[0021] In order to more clearly demonstrate the above and other purposes, features and advantages of the present invention, the embodiments of the present invention are described in detail below, but they are not intended to limit the invention in any way.
[0022] The idea of the present invention is to introduce a material with high theoretical capacity for reversible lithium storage and low potential for reversible lithium storage during the preparation of the positive electrode material to obtain a composite positive electrode material with a core-shell structure.
[0023] The specific constitution of the core-shell composite positive electrode material of the present invention is that the material with high reversible lithium storage theoretical capacity and low reversible lithium storage potential is tightly wrapped by the positive electrode material.
[0024] The material with high reversible lithium storage theoretical capacity and low reversible lithium storage potential used for preparing the core-shell composite positive electrode material of the present invention is one or more of silicon, graphene, graphene oxide, graphite, graphite oxide, germanium, tin, phosphorus and antimony.
[0025] The conventional positive electrode material used in the present invention is one of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material and nickel-cobalt-aluminum ternary material.
[0026] When the aforementioned core-shell composite positive electrode material is used to assemble a lithium-ion battery, the negative electrode material can be graphite, a carbon-silicon composite material, metallic lithium, graphene, or graphene oxide.
[0027] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used in the following are conventional reagents, conventional materials and conventional instruments, which can be purchased through normal channels.
[0028] Embodiment 1:
[0029] The material of high reversible lithium storage theoretical capacity and low reversible lithium storage potential in this embodiment is silicon powder, and the positive electrode material is lithium iron phosphate;
[0030] Mix water and ethylene glycol in a volume ratio of 1:1, and ultrasonically disperse silicon powder therein;
[0031] Add ferrous sulfate and phosphoric acid into the above mixed solvent system, and introduce argon gas to stir evenly;
[0032] The prepared lithium hydroxide solution was slowly added dropwise into the above solution system, and argon gas was continuously introduced during the process;
[0033] After the addition was completed, the pH was adjusted to 7.3, and a solvothermal reaction was carried out at 120°C;
[0034] The solvent thermal reaction product is washed, centrifuged, and dried, then ground and mixed with glucose and polyethylene glycol, and calcined at 750° C. in an argon atmosphere for 2 hours to obtain the product composite cathode material.
[0035] Embodiment 2:
[0036] The material of high reversible lithium storage theoretical capacity and low reversible lithium storage potential in this embodiment is silicon powder, and the positive electrode material is lithium iron phosphate;
[0037] Mix water and propylene glycol in a volume ratio of 1:1, and ultrasonically disperse silicon powder therein;
[0038] Add ferrous sulfate and phosphoric acid into the above mixed solvent system, and introduce argon gas to stir evenly;
[0039] The prepared lithium hydroxide solution was slowly added dropwise into the above solution system, and argon gas was continuously introduced during the process;
[0040] After the addition was completed, the pH was adjusted to 7.3, and a solvothermal reaction was carried out at 120°C;
[0041] The solvent thermal reaction product is washed, centrifuged, and dried, then ground and mixed with glucose and polyethylene glycol, and calcined at 750° C. in an argon atmosphere for 2 hours to obtain a composite cathode material.
[0042] Embodiment 3:
[0043] The material of high reversible lithium storage theoretical capacity and low reversible lithium storage potential in this embodiment is silicon powder, and the positive electrode material is lithium cobalt oxide;
[0044] Mix water and ethylene glycol in a volume ratio of 1:1, and ultrasonically disperse silicon powder therein;
[0045] Add cobalt nitrate into the above mixed solvent system and stir evenly;
[0046] Slowly add ammonia water into the above solution system while stirring continuously;
[0047] The precipitated cobalt hydroxide is collected, washed, centrifuged, and dried, then mixed with lithium hydroxide by ball milling, and calcined at 900° C. in an oxygen atmosphere for 6 hours to obtain a composite positive electrode material.
[0048] Embodiment 4:
[0049] The material with high reversible lithium storage theoretical capacity and low reversible lithium storage potential in this embodiment is graphene oxide, and the positive electrode material is lithium iron phosphate;
[0050] Water and ethylene glycol are mixed in a volume ratio of 1:1, and graphene oxide is ultrasonically dispersed therein;
[0051] Add ferrous sulfate and phosphoric acid into the above mixed solvent system, and introduce argon gas to stir evenly;
[0052] The prepared lithium hydroxide solution was slowly added dropwise into the above solution system, and argon gas was continuously introduced during the process;
[0053] After the addition was completed, the pH was adjusted to 7.3, and a solvothermal reaction was carried out at 120°C;
[0054] The solvent thermal reaction product is washed, centrifuged, and dried, then ground and mixed with glucose and polyethylene glycol, and calcined at 750° C. in an argon atmosphere for 2 hours to obtain the product composite cathode material.
[0055] Embodiment 5:
[0056] The composite positive electrode material prepared in Example 1 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the positive electrode material loading was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0057] Embodiment 6:
[0058] The composite positive electrode material prepared in Example 1 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the positive electrode material loading was 40 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0059] Embodiment 7:
[0060] The composite positive electrode material prepared in Example 3 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the positive electrode material loading was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0061] Embodiment 8:
[0062] The composite positive electrode material prepared in Example 4 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the positive electrode material loading was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0063] Comparative Example 1:
[0064] The difference between Comparative Example 1 and Example 5 is that silicon powder is not added when preparing the positive electrode material.
[0065] Comparative Example 2:
[0066] The difference between Comparative Example 2 and Example 6 is that silicon powder is not added when preparing the positive electrode material.
[0067] Comparative Example 3:
[0068] The difference between Comparative Example 3 and Example 7 is that silicon powder is not added when preparing the positive electrode material.
[0069] Comparative Example 4:
[0070] The difference between Comparative Example 4 and Example 8 is that graphene oxide is not added when preparing the positive electrode material.
[0071] The batteries assembled in Examples 5 to 8 and Comparative Examples 1 to 4 were subjected to constant current charge and discharge characterization, the batteries assembled in Example 5 and Comparative Example 1 were subjected to electrochemical impedance testing, and the batteries assembled in Example 5 and Comparative Example 1 were subjected to cyclic voltammetry testing.
[0072] Figure 1 Schematic diagram of the mechanism of additional reversible lithium storage of the core-shell composite positive electrode material prepared in Example 1.
[0073] Figure 2 is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 5 and the lithium-ion battery assembled in Comparative Example 1, Figure 2 It can be seen that the specific capacity of the lithium-ion battery assembled in Example 5 reaches 187 mAh g at a rate of 0.1C. -1 , exceeding the theoretical capacity of lithium iron phosphate, while the lithium-ion battery assembled in Comparative Example 1 has a specific capacity of 162 mAh g at a rate of 0.1C. -1 , indicating that the silicon present in the core-shell composite positive electrode material prepared in Example 1 has a great positive effect on improving the specific capacity.
[0074] Figure 3 is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 6 and the lithium-ion battery assembled in Comparative Example 2, Figure 3 It can be seen that the specific capacity of the lithium-ion battery assembled in Example 6 reaches 156 mAh g at a rate of 0.1C. -1 , while the lithium-ion battery assembled in Comparative Example 2 has a specific capacity of only 130 mAh g at a rate of 0.1C. -1 Although the capacity of the lithium-ion battery assembled in Example 6 is lower than that of the lithium-ion battery assembled in Example 5, which may be caused by the problem of slowing kinetics after the electrode is thickened, it is still much higher than the specific capacity of the lithium-ion battery assembled in Comparative Example 2, indicating that the silicon present in the core-shell composite positive electrode material prepared in Example 1 has a great positive effect on the improvement of the specific capacity.
[0075] Figure 4 : is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 7 and the lithium-ion battery assembled in Comparative Example 3, Figure 4 It can be seen that the specific capacity of the lithium-ion battery assembled in Example 7 reaches 176 mAh g at a rate of 0.1C. -1 , while the lithium-ion battery assembled in Comparative Example 2 has a specific capacity of only 155 mAh g at a rate of 0.1C. -1 The silicon in the core-shell composite positive electrode material prepared in Example 3 has a great positive effect on the improvement of the specific capacity, and it also shows that this structure is applicable to lithium iron phosphate and lithium cobalt oxide positive electrode material systems.
[0076] Figure 5 is a comparison chart of the constant current charge-discharge cycle performance of the lithium-ion battery assembled in Example 8 and the lithium-ion battery assembled in Comparative Example 4, Figure 5 It can be seen that the specific capacity of the lithium-ion battery assembled in Example 8 reaches 174 mAh g at a rate of 0.1C. -1 , while the lithium-ion battery assembled in Comparative Example 4 has a specific capacity of only 155 mAh g at a rate of 0.1C. -1 , indicating that the graphene oxide present in the core-shell composite positive electrode material prepared in Example 4 has a positive effect on improving the specific capacity.
[0077] Figure 6 is a cyclic voltammetry comparison diagram of the lithium ion battery assembled in Example 5 and the lithium ion battery assembled in Comparative Example 1, Figure 6 It can be seen that the cyclic voltammetry curve of the lithium ion battery assembled in Example 5 has an additional pair of redox peaks compared with the cyclic voltammetry curve of the lithium ion battery assembled in Comparative Example 1, corresponding to the additional redox reaction. At the same time, the integrated area of the cyclic voltammetry curve of the lithium ion battery assembled in Example 5 is greater than that of Comparative Example 1, indicating that the silicon in the composite positive electrode material does participate in the redox reaction in this potential range, providing additional capacity.
[0078] Figure 7 is a differential comparison diagram of the constant current charge and discharge curves of the lithium ion battery assembled in Example 5 and the lithium ion battery assembled in Comparative Example 1, Figure 7 It can be seen that the differential graph of the constant current charge and discharge curve of the lithium ion battery assembled in Example 5 has an additional pair of peaks compared with the differential graph of the constant current charge and discharge curve of the lithium ion battery assembled in Comparative Example 1, corresponding to the additional redox reaction, indicating that the silicon in the composite positive electrode material does participate in the redox reaction in this potential range, providing additional capacity.
[0079] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A method for increasing the capacity of a lithium battery positive electrode material, characterized in that: In the process of preparing the positive electrode material, a material with high theoretical capacity for reversible lithium storage and low potential for reversible lithium storage is introduced to obtain a composite positive electrode material with a core-shell structure; The specific composition of the composite positive electrode material of the core-shell structure is that the material with high reversible lithium storage theoretical capacity and low reversible lithium storage potential is tightly wrapped by the positive electrode material; The material with high reversible lithium storage theoretical capacity and low reversible lithium storage potential is silicon or graphene oxide; The positive electrode material is lithium iron phosphate; The steps for preparing the composite positive electrode material with a core-shell structure are as follows: Water and ethylene glycol are mixed in a volume ratio of 1:1, and material powder with high reversible lithium storage theoretical capacity and low reversible lithium storage potential is ultrasonically dispersed therein; Add ferrous sulfate and phosphoric acid into the above mixed solvent system, and introduce argon gas to stir evenly; The prepared lithium hydroxide solution was slowly added dropwise into the above solution system, and argon gas was continuously introduced during the process; After the addition was completed, the pH was adjusted to 7.3, and a solvothermal reaction was carried out at 120°C; The solvent thermal reaction product is washed, centrifuged, and dried, then ground and mixed with glucose and polyethylene glycol, and calcined at 750° C. in an argon atmosphere for 2 hours to obtain a composite cathode material.
2. Large capacity lithium-ion batteries, including: The positive electrode and the negative electrode are characterized in that the positive electrode is a composite positive electrode material with a core-shell structure prepared by the method for improving the capacity of the positive electrode material of a lithium battery as described in claim 1.
3. The large-capacity lithium-ion battery according to claim 2, characterized in that: The negative electrode material is one of graphite, carbon-silicon composite material, metallic lithium, graphene, and graphene oxide.
Citation Information
Patent Citations
Core-shell composite anode material for lithium ion battery and preparation method thereof
CN101740752A
Preparation method for carbon-silicon coated lithium iron phosphate composite material for lithium ion battery
CN105609716A